IMPLEMENTATION OF QANUN NUMBER 6 OF 2014 CONCERNING JINAYAT MAISIR LAW IN BANDA SAKTI DISTRICT, LHOKSEUMAWE CITY - Yunda Mardiati; Teuku Alfiady; Aflia Riski; Aiyub; Murniati (RADJA PUBLIKA, 2025)
Gambling/maisir activities in Banda Sakti District, Lhokseumawe City oppose the implementation of Qanun Number 6 of 2014 concerning the Jinayat Maisir Law in force in Aceh Province. This study aims to analyze the extent to which the implementation of this Qanun has been carried out and to identify the factors that are obstacles in its implementation. The method used is a descriptive qualitative approach, with data collection techniques through interviews, observations, and documentation of law enforcement officers, religious figures, academics, and the community. The results of the study indicate that the implementation of the Qanun has not been running optimally. This can be seen from the still high number of gambling cases in Banda Sakti District. The communication aspect is considered ineffective because the dissemination of information is limited to sticker media and socialization to schools, without utilizing digital channels that are more relevant to the characteristics of today's society. In addition, limited human resources and budget are obstacles to supervision and law enforcement. The lack of disposition and commitment from the authorities is also an obstacle in the implementation of this policy. A more modern, collaborative and participatory communication approach is needed, as well as increasing the capacity of legal apparatus and infrastructure so that this qanun can be implemented consistently and effectively.